THERAPEUTIC CAPACITIES OF HUMOR WHEN DEALING WITH CHILDREN IN THE NEGATIVE PSYCHIC STATE OF MIND - Gordiienko-Mytrofanova, Iia; Kobzieva, Iuliia (PSYCHOLOGICAL JOURNAL, 2018)
The article is devoted to the development of the conceptual foundation for the technique of therapeutic humor, which is intended to harmonize the relationships between parents and their children (pre-school students) who experience negative psychic states of mind. The theoretical reasoning behind the therapeutic potential of the “positive reinterpretation” method and Pollyanna principles, which are especially important for securing children’s mental health, together with the systematization of psychological approaches to the development of humor in children, and the psycholinguistic experiment whose aim was to define the semantic clusters of the stimulus-word “humor”- all these enabled us to outline the conceptual underpinning for the technique of therapeutic humor, which involves the following: - method of “positive reinterpretation” that focuses, in the first place, on the parents’ ability to understand the “positive” aspects of deviations, i.e. the child’s ability to react to particular situations and conflicts displaying particular symptomatic behavior, and secondly, it means parents’ direct involvement into the process of correcting their child’s behavior, i.e. helping the child to give up unhealthy relationships with oneself and the rest of the world and take up more healthy and adaptive formats; - Pollyanna’s “Glad game”, whose aim is to reduce the child’s level of emotional suffering and enhance the feeling of well-being via developing a more positive attitude to life; - “prevention of humor misunderstanding”, which is aimed at teaching parents to feel their child on the basis of recollecting their own childhood memories connected with traumatic humor misunderstanding. This helps to better understand the child’s emotions; - reading and discussing children’s humoristic literature together with the child. This activity helps to establish closer relationships between parents and children, building the atmosphere of trust and friendship; - children’s psychotherapy is performed through the psychotherapy of their parents. The main goal of the therapeutic humor technique is to help children to deal with their symptomatic behavior via direct involvement of their parents into the process of correcting their child’s behavior.